2006
DOI: 10.1111/j.1525-1438.2006.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of loop electrosurgical excision procedure for cervical neoplasia in human immunodeficiency virus-infected women

Abstract: The objective of this study was to evaluate the treatment outcomes and complications in human immunodeficiency virus (HIV)-infected women undergoing loop electrosurgical excision procedure (LEEP) for cervical neoplasia. The medical record of 60 evaluable HIV-infected women who had abnormal Papanicolaou (Pap) smear and underwent LEEP following colposcopy at Chiang Mai University Hospital between May 1998 and June 2004 was reviewed. Thirty-one (51.7%) had associated genital infection at screening. Twenty-five (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 39 publications
10
37
0
Order By: Relevance
“…Our overall cure rate of 94% compares favorably with the 90%-95% from nonrandomized studies [1][2][3][4][5][6]8]. Adverse effects and complications were observed in a negligible proportion of women and none were major or life threatening, which is similar to those reported in other studies [1][2][3][4][5][6][7][8][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…Our overall cure rate of 94% compares favorably with the 90%-95% from nonrandomized studies [1][2][3][4][5][6]8]. Adverse effects and complications were observed in a negligible proportion of women and none were major or life threatening, which is similar to those reported in other studies [1][2][3][4][5][6][7][8][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the present study and those from other low-income country settings [8,20,21] reinforce that LEEP can be performed effectively in these settings with a low frequency of complications and high rates of disease control. The widespread use of LEEP to treat CIN that requires excision should be an important integral component of screening programs in low-income countries.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, adverse effects and complications following LEEP were observed in a negligible proportion of women and none were major or life threatening. The frequency of adverse effects and complications favorably compares with those reported from other studies in both high-and low-income countries [1][2][3][4][5][6][7]20,21].…”
Section: Discussionsupporting
confidence: 77%
“…In a study of 60 HIV-infected women receiving LEEP in Thailand, no significant difference in complications could be demonstrated between HIV-infected women and the control group nor between HIV-infected women receiving antiretroviral therapy and those not receiving antiretroviral therapy [22]. We confirm the safety profile of LEEP in HIV-infected women in a resource-constrained setting with the largest such cohort reported based on our review of the English language medical literature.…”
Section: Discussionsupporting
confidence: 72%